Potensi Minyak Atsiri Kulit Buah Jeruk Nipis untuk Pengendalian Crocidolomia Pavonana - Nidia Melati Al Anshori; Retno Wijayanti; Ato Sulistyo (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Cabbage head caterpillar (Crocidolomia pavonana) is a major pest on Brassicaceae. Control using chemical insecticides to control this pest can resistance. When used as a lime peel essential oil is thought to be cabbage head caterpillar pest control compounds that contain monoterpene. This study is conducted in August 2016- January 2017. This study used a completely randomized design (CRD) with one factor is the concentration of essential oil. Variables measured were Larvicide, antifeedant, antioviposition, and phytotoxocity. The research results showed that essential oil of lime peel cause mortality of larvae of C. pavonana slowly. antifeedant activity due to the essential oil of less than 50%. Inhibition of egg laying was significant at concentration of 0.2% (73.3%),0.8% and 1.6% (80%). Essential oil causes necrosis of leaf less than 10%.